Effect of attentional bias modification on pre-competition anxiety in athletes - Zhao, Jing; Yang, Yuhan; Zhang, Heng; Nie, Yu; Wang, Qiulin (Frontiers in Psychology, 2025)
BackgroundUnder high-pressure situations, such as crucial games, some athletes often underperform. This is the case even for exceptional athletes in critical moments of competition. Athletes often experience performance anxiety, which creates attentional errors and underperformance. Attentional bias, where emotional stimuli influence decision-making, may also result in selective attention to negative information. Attentional bias correction training (ABMT) aims to modify these attention patterns with the aim of alleviating anxiety symptoms. In this study, we investigated the pre-competition attention patterns among high-level athletes to enhance performance.MethodsAttentional bias correction training was employed to train 32 athletes for 4 weeks, every 2 days (emotional pictures for the experimental group and star pictures for the control group). A point detection paradigm was also utilized to test the athletes’ attentional bias behavior in a pre-competition anxiety situation before and after training.ResultsThe results revealed a significant main effect of test time on self-rated anxiety level of high-level athletes (F(1, 32) = 204.072, p < 0.001, η2p = 0.919), while the main effect of group was not significant (F(1, 32) = 0.505, p > 0.05, η2p = 0.025). Moreover, significant interaction was recorded between the test time and group (F(1, 32) = 124.895, p < 0.001, η2p = 0.874). In the simple effects analysis, high-level athletes in the experimental group had significantly lower pre-competition anxiety scores at the post-test than at the pre-test (43.90 ± 2.57 vs. 57.00 ± 2.77, p < 0.001). However, for the control group, there was no significant difference between the two groups (52.20 ± 2.57 vs. 53.80 ± 2.77, p = 0.133). In addition, the attentional bias scores were significantly different before and after the training (5.985 ± 1.045 vs. -0.613 ± 0.60, p < 0.05) in the experimental group, whereas there were no significant differences in the control group (7.813 ± 1.045 vs. 5.773 ± 0.613, p > 0.05).ConclusionThe present findings demonstrate that attentional bias correction training can effectively reduce pre-match anxiety and attentional bias toward negative information in high-level athletes. These results provide an important foundation for enhancing pre-competition attention training and mood regulation in athletes. Future research should explore the underlying mechanisms and practical applications of these findings to facilitate the development of strategies to improve pre-match attention training.